(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Since the declaration of COVID-19 pandemic by WHO on 13 March2020, over 210 countries / territories have had active cases and 1/3rd of the world’s population have been on complete lockdown or partial restriction. Main route of transmission of COVID-19 is through droplets like most communicable respiratory illnesses followed by infected surfaces. Public measures like wearing masks, social distancing, hand washing and other respiratory hygiene are being followed in unprecedented level and people are tested rapidly if they show symptoms of the disease such as fever, cough, fatigue, myalgia and dyspnea. These symptoms are similar to other respiratory diseases such as common flu, influenza, pneumonia and Tuberculosis. The preventive measures are also effective in these diseases. In Wuhan, China the lockdown lasted for 76 days and seems to follow similar course in other countries. The air pollution and travel has also decreased which will further decrease transmission of respiratory illnesses. These behavioral changes can get embedded into human cultures and play a vital role to decrease incidence of other respiratory illnesses. To measure the impact, we need to be observant and carry time series analysis of the pre and post pandemic data. With proper strategies this could be utilized as an opportunity to reduce burden of other respiratory communicable disease.